The Effect of Bitter Orange Aroma Therapy on Reducing Pain Intensity in Labor Multigravids at Clinik Masitah Year 2023 - Imbi Hera Novita; Eli Rahmawati; Ernani Setyawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Pain labor can increase emotional stress on the birthing mother, and can cause fatigue and can have an impact on abnormal uterine muscle function during labor leading to birth complications. One of the non-pharmacological therapies to reduce labor pain is bitter orange aromatherapy, which is a non-pharmacological therapy to reduce or relieve pain in mothers who give birth in the first stage. The type of research used in this research is a quasi experiment with a nonequivalent control group design. Sampling used purposive sampling technique as many as 22 people. Data collection used a visual analog scale pain measuring instrument, data analysis used the Wilcoxon test. The results of the study showed that there was a difference in decreasing the intensity of the pain scale in stage 1 before and after administering bitter orange aroma therapy with a p-value (0.003) and an α value (0.05). Labor pain is caused by contractions of the uterine muscles, stretching of the uterine muscles and psychological conditions, in this case fear, anxiety and tension which can trigger the production of prostaglandine hormones, causing stress. Stress conditions can affect the body's ability to withstand pain. One way to treat pain in birthing mothers is by using non-pharmacological methods by administering bitter orange aromatherapy. Bitter orange aroma therapy influence the decline intensity pain in the first stage of multigravida labor active in the clinic still in 2023